Ruang Lingkup Metode Pembelajaran - Riza, Safrur; Barrulwalidin, Barrulwalidin (ISLAMIC PEDAGOGY: Journal of Islamic Education, 2023)
A learning method is a set of strategies, techniques, and approaches used in the teaching and learning process to help students understand and master the subject matter. The scope of learning methods includes various aspects of the learning process, such as curriculum design, selection and use of learning media, subject matter development, learning evaluation, and classroom management. The scope of learning methods includes (1) facilities/tools, (2) students, and (3) teaching materials/study materials. Therefore, a good understanding of the scope of learning methods is essential for teachers, curriculum developers, and other educational practitioners to improve the quality of the learning process and achieve the desired learning goals.